ANALISIS BERPIKIR KREATIF PADA PENERAPAN PROBLEM BASED LEARNING BERPENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS - Ariani, Liska; Sudarmin, Sudarmin; Nurhayati, Sri (Jurnal Inovasi Pendidikan Kimia, 2019)
This study aims to analyze the ability of students’ creative thinking through the application of Problem Based Learning Model based on Science, Technology, Engineering, and Mathematics (STEM) on solubility and solubility product constant (Ksp) material. The research method used was a case study with One-Shot Case Study design. Sampling in this research using purposive sampling technique. Instruments data collection using test method in the form questions of creative thinking to know the ability of students creative thinking and questionnaire to know the students response to the learning had done. The results showed that, the average ability of creative thinking of students in good criteria with score 47,84 from total score 60 and the highest achievement in the indicator to view information from different point of view (89,48%), and the students gave positive responses for learning which is done. The conclusion of theses researches is the student’s ability of creative thinking after applied Problem Based Learning Model based on Science, Technology, Engineering, and Mathematics on solubility and solubility product constant (Ksp) material in good criteria.